Terapi Musik sebagai Terapi Komplementer untuk Menurunkan Kecemasan Pasien - Yuliasih Yuliasih; Sri Yona; Agung Waluyo (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the effectiveness of music therapy in reducing anxiety in patients in the intensive care unit. The research method uses article searches conducted on four databases, namely Science Direct, Embase, Pubmed, and Proquest, with the keywords "Anxiety," "therapy music," and "Intensive Care Unit." Articles are limited to the last ten years, English, free full text, RCT, or clinical trial designs. Of the 500 articles obtained, after screening, eight articles were subjected to further analysis. The study results show that music therapy positively impacts the physical and psychological aspects of patients in the intensive care unit. The positive impact from a biological perspective includes lowering the respiratory and heart rates, while the positive effects from a psychological perspective are reducing anxiety. The effective duration of music therapy in reducing stress after analysis is 25-90 minutes. In addition, there is no significant difference in the type of music in reducing anxiety. In conclusion, music therapy can be used as a complementary therapy in reducing patient anxiety in the intensive care unit because it is proven to reduce stress, has minimal side effects, and is inexpensive. Keywords: Anxiety, Intensive Care Unit, Music Therapy